Transformasi Pesantren dalam Era Digital: Peluang dan Tantangan dalam Aspek Dakwah dan Pendidikan - Ibad, Nashoihul; Novianto Puji Raharjo (Masjiduna : Junal Ilmiah Stidki Ar-Rahmah, 2024)
ABSTRACT Islamic boarding schools as traditional Islamic educational institutions in Indonesia face a digital era that brings significant changes. Digital transformation offers various opportunities such as increased access to learning resources and the expansion of da'wah networks. However, challenges such as the digital divide and curriculum adaptation are also major concerns. This article aims to explain how the concept of digital transformation for Islamic boarding schools faces the current digital era. Digital transformation opportunities for Islamic boarding schools can bring technological advances to Islamic boarding schools. However, the challenge for pesantren must also be ready regarding technological infrastructure and how to manage the negative impact of the digital era on pesantren culture. Therefore, a comprehensive strategy is needed to optimize opportunities and overcome challenges in this digital era. This article will describe how opportunities can be taken for pesantren management so that it can expand the social network of pesantren and discuss effective strategies. Furthermore, in further discussion, some data will be presented that shows the success of case studies of pesantren that can integrate pesantren technology in the digital era. The conclusion from this article that can be drawn is that pesantren need to face digital transformation and adapt in the digital era. Among them is being able to integrate the use of technology for the learning process, improving the ability of educators and the socio-cultural adaptation process in Islamic boarding schools. Keywords: Digital, Islamic Boarding School, Transformation